Characteristics of cervical myofascial pain in medical students - Samatra, Dewa Putu Gede Purwa; Widyadharma, I Putu Eka; Haditya, Yogi; Suryamulyawan, Kadek Adi; Devi, Gusti Ayu Putu Giti Livia; Lim, Demetria Jesica; Wijayanti, Ida Ayu Sri; Adnyana, I Made Oka; Purwata, Thomas Eko (DiscoverSys Inc., 2019)
Background: Cervical myofascial pain or neck pain is in the fourth most disease that causes disability after back pain, depression, and other musculoskeletal diseases. Cervical myofascial pain is characterized by pain originating from a trigger point located in the skeletal muscle, commonly referred as myofascial trigger points (MTrPs).Methods: An observational study with a cross-sectional design, conducted on 3 to 9 of December 2018 with research subjects were medical students at Udayana University who undergoing 5th and 6th year in clinical clerkship at Sanglah General Hospital Denpasar. The data was taken using Google Form which was filled in online by the subject and then analyzed using SPSS version 21.Results: From 307 respondents, 62.2% stated experiencing neck pain (196 respondents) with the majority of women 65.4%, the duration of neck pain occurred for <24 hours with the most frequent frequency at least once per month (46.1%), and appeared most often at night (39.8%) and occurs after night shift in 106 subjects (55.5%). The pain was said getting worse by activity in 102 subjects (52.4%) and getting better when resting in 185 subjects (96.9%). Most of the subjects did not use pain relievers to treat neck pain experienced (84.3%). In subjects who use painkillers, Paracetamol is the most often drug of choice to relieve pain (11%). For non-pharmacological treatment, 53.4% of respondents chose to rest or sleep.Conclusion: Most of the respondents who were clerkship reported experiencing neck pain at least once a month and often felt after a night shift. Respondents who reported neck pain were mostly women.